2022
DOI: 10.3389/fcell.2022.795784
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Migratory Patterns: Implications for Cardiovascular Disease

Abstract: The body’s inflammatory response involves a series of processes that are necessary for the immune system to mitigate threats from invading pathogens. Leukocyte migration is a crucial process in both homeostatic and inflammatory states. The mechanisms involved in immune cell recruitment to the site of inflammation are numerous and require several cascades and cues of activation. Immune cells have multiple origins and can be recruited from primary and secondary lymphoid, as well as reservoir organs within the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 217 publications
(268 reference statements)
0
2
0
Order By: Relevance
“…Neutrophils are the major pathogen fighting immune cells, functioning as regulators of innate and adaptive immune responses ( Mayadas et al, 2014 ). Neutrophils are major contributors in the pathogenesis of various autoimmune diseases, autoinflammatory syndromes, and cardiovascular diseases ( Dahdah et al, 2022 ; Kaplan, 2013 ; Wouters et al, 2021 ). Eosinophils are also involved in the immunological regulation of both innate and adaptive immunity ( Wen & Rothenberg, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are the major pathogen fighting immune cells, functioning as regulators of innate and adaptive immune responses ( Mayadas et al, 2014 ). Neutrophils are major contributors in the pathogenesis of various autoimmune diseases, autoinflammatory syndromes, and cardiovascular diseases ( Dahdah et al, 2022 ; Kaplan, 2013 ; Wouters et al, 2021 ). Eosinophils are also involved in the immunological regulation of both innate and adaptive immunity ( Wen & Rothenberg, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that neutrophils, neutrophil-derived IL-8 and NETs elements were elevated in plasma and tissue of patients with AAA suggesting enhanced neutrophil activation ( 18 , 33 , 34 ). The recruitment of neutrophils is facilitated by CXCL1, CCL2, CCL5 and CXCL8 chemokines ( 22 , 39 ) that are mainly produced by pro-inflammatory macrophages and are elevated in serum and aorta from humans ( 40 42 ) and mice with AAA ( 43 ). The depletion of neutrophils or genetic ablation of neutrophil-specific genes (e.g., MPO, MMP-9) attenuates AAA development, suggesting overall pathogenic role for these cells in AAA ( 3 , 19 , 44 , 45 ).…”
Section: Immune Cells In Abdominal Aortic Aneurysmmentioning
confidence: 99%